Assessment of potential drug-drug interactions in patients with hereditary angioedema from the ITACA cohort: simulations from a real-life dataset considering danazol versus berotralstat - Zanichelli, Andrea; Cattaneo, Dario; Gidaro, Antonio; Senter, Riccardo; Arcoleo, Francesco; Accardo, Pietro; Bignardi, Donatella; Borrelli, Paolo; Colangelo, Caterina; De Pasquale, Tiziana; Firinu, Davide; Perego, Francesca; et al. (Frontiers in Pharmacology, 2025)
BackgroundDanazol is regularly used as a prophylactic treatment in patients with Hereditary angioedema due to C1-inhibitor deficiency (HAE-C1INH). However, this drug is characterized by a risk of drug-drug interactions (DDIs). Berotralstat, the first oral kallikrein inhibitor, has been recently approved for the prevention of HAE attacks. Here, we sought to compare the risk of potential DDIs in real-life HAE patients hypothetically given Danazol or Berotralstat.MethodsOur clinic’s database was retrospectively reviewed to identify patients diagnosed with HAE who were treated with at least one concomitant medication. The DDIs were assessed using three freely available drug interaction checkers and scored based on their severity. The agreement between the three drug checkers was evaluated using weighted Cohen’s kappa coefficient.Results75 HAE patients (64% female, mean age 56 ± 21 years) were considered. They were mainly treated with antihypertensives (37%), hypoglycemic (19%), and hypolipemic agents (17%). Significant discrepancies among the three-drug interaction checkers were found. The first checker identified 18 potential DDIs, all involving Danazol and a statin (simvastatin). The second checker identified, respectively, 66 and 14 DDIs for Danazol (20% severe, regarding Simvastatin and Rivaroxaban) and Berotralstat (0% severe). The third checker identified 49 and 43 DDIs for Danazol (22% severe, regarding Simvastatin) and Berotralstat (0%).ConclusionBerotralstat was consistently associated with a reduced risk of DDIs compared with Danazol. A rational assessment of DDIs would help select the best prophylactic treatment for HAE.